2008
DOI: 10.1086/593196
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils May Be a Vehicle for Viral Replication and Dissemination in Human H5N1 Avian Influenza

Abstract: The mechanism of systemic spread of H5N1 virus in patients with avian influenza is unknown. Here, H5N1 nucleoprotein and hemagglutinin were identified by immunohistochemistry in the nucleus and cytoplasm of neutrophils in the placental blood of a pregnant woman. Viral RNA was detected in neutrophils by in situ hybridization and enhanced real-time polymerase chain reaction. Therefore, neutrophils may serve as a vehicle for viral replication and transportation in avian influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 20 publications
0
41
0
4
Order By: Relevance
“…Neutrophils exposed to influenza virus undergo activation of the respiratory burst, followed by depression of cell function when subsequently exposed to secondary stimuli (69), although innate defense proteins of the collectin family have been shown to protect neutrophils from these depressive effects (70). Neutrophils themselves have been reported as both nonpermissive (6) and susceptible to influenza virus infection (71,72) and to respond to virus exposure via TLR7-and/or TLR8-mediated production of proinflammatory cytokines (71). Neutrophil granules, including azurophil/primary, secondary, and secretory granules, contain an array of molecules with potential for antiviral activity, including ␣ and ␤ defensins and pentraxins, which have been shown to exert antiviral activities against a range of viruses, including influenza (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils exposed to influenza virus undergo activation of the respiratory burst, followed by depression of cell function when subsequently exposed to secondary stimuli (69), although innate defense proteins of the collectin family have been shown to protect neutrophils from these depressive effects (70). Neutrophils themselves have been reported as both nonpermissive (6) and susceptible to influenza virus infection (71,72) and to respond to virus exposure via TLR7-and/or TLR8-mediated production of proinflammatory cytokines (71). Neutrophil granules, including azurophil/primary, secondary, and secretory granules, contain an array of molecules with potential for antiviral activity, including ␣ and ␤ defensins and pentraxins, which have been shown to exert antiviral activities against a range of viruses, including influenza (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of neutrophils to internalize viruses was investigated by confocal microscopy (Mohamadzadeh et al, 2006), PCR (Larochelle et al, 1998;Gerna et al, 2000;Zhao et al, 2008), flow cytometry (Hufford et al, 2012), and immunochemistry (Zhao et al, 2008) to detect the presence of viral-associated molecules and particles (Hackemann et al, 1974;Larochelle et al, 1998). The development of green fluorescent protein-tagged viruses also allowed the visualization of internalized viruses (Duffy et al, 2012;Hufford et al, 2012).…”
Section: Virus Internalization and Replicationmentioning
confidence: 99%
“…While murine neutrophils are not susceptible to influenza virus (Tate et al, 2011) and alphavirus (Levitt et al, 1979) infections, human neutrophils are susceptible to these viruses (Abramson et al, 1982b(Abramson et al, , 1986Zhao et al, 2008) and others, such as MARV (Mohamadzadeh et al, 2006), EpsteinBarr virus (EBV) (Larochelle et al, 1998), and RSV (Halfhide et al, 2011). Viruses may enter human neutrophils by endocytosis or phagocytosis.…”
Section: Virus Internalization and Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…e mechanism of systemic spread of H5N1 virus in patients with avian in�uenza is unknown. Based on immunohistochemical �ndings of H5N1 nucleoprotein and hemagglutinin in the nucleus and cytoplasm of neutrophils in the placental blood of a pregnant woman, it was suggested that neutrophils could serve as a vehicle for viral replication and transportation in avian in�uenza [166].…”
Section: Dcs Suppress Immune Responses Through the Generation Of Foxp3mentioning
confidence: 99%